Sewage Sludge Conditioning using Opuntia Ficus Indica Juice - Betatache, Hayat; Aouabed, Ali (Revue des sciences de l’eau / Journal of Water Science, 2015)
This work aimed to study the possibility of using plant matter, Opuntia ficus indica juice (OFIJ), for conditioning the Beni-Messous (Algiers) wastewater treatment plant sludge. The optimum dosage of OFIJ was found to be 0.4 g⋅kg‑1 of dry matter, for which the residual turbidity, the dryness of the filtration cake, and the specific resistance of filtration were found to be 2.5 NTU, 24% and 0.13⋅1012m⋅kg‑1, respectively. The results obtained with OFIJ are also compared with those of commercial polyelectrolytes such as Chimfloc C4346, a cationic polymer, Sedipur NF 400, a non-ionic polymer, and Sedipur AF 102, an anionic polymer, and inorganic conditioners such as FeCl3 and Al2(SO4)3. OFIJ proved to be the most efficient because the optimum dosage was found to be 0.4 g⋅kg‑1 of dry matter for OFIJ whereas for Chimfloc C4346, FeCl3 and Al2(SO4)3 the optimum doses were be found to be 0.8, 80 and 60 g⋅kg‑1. Based on the obtained results, OFIJ could be used as a natural conditioner in sewage sludge treatment.